Exploration of indigenous arbuscular mycorrhizal fungi in saline soil. - Haryantini, Baiq Azizah; Nurbaity, Anne; Simarmata, Tualar (Journal of Tropical Mycorrhiza, 2024)
High concentration of salt in saline soil inhibits plants to grow normally. Good management of this soil may improve this land to be more productive. Utilization of indigenous beneficial soil microorganisms such_ as arbuscular mycorrhizal fungi (AMF) isolated from saline soil has been known to be able to increase plant growth and mycorrhizal sporulation. This study aimed to explore indigenous AMF species in saline soil, in West_ Java. This research was conducted in salt impacted areas in the northern coastal area of West Java i.e. Karawang, Subang, Indramayu, and Cirebon. The method used for soil sampling is by transect with the length of ordinate point in every 500 m of the coastline. The number of AMF spores, mycorrhizal colonization, and mycorrhizal species identification were analyzed. The result showed that the number of indigenous AMF spores per 25 g soil were 109 in Karawang, 50 in Indramayu, 170 in Subang, and 100 in Cirebon. The average mycorrhizal colonization was 90 %. Glomus sp. and Gigaspora sp. were found to be dominant in those soils. This result implies that some mycorrhizal fungi can live and maybe had good adaptation in saline soil and from symbiosis activity with the plant. Therefore they are the potential to evaluated and used to improve saline land productivity in the future.